Henry Justin Allen papers - Allen, Henry Justin, 1868-1950.
Correspondence, speeches, articles, clippings, printed matter, and other papers relating to Allen's public career, especially his terms as governor of and U.S. senator from Kansas. Documents Allen's business activities; his work on behalf of Great Lakes-St. Lawrence Tidewater Association, Near East Relief, and Save the Children (U.S.); and family affairs. Subjects include the debate between Allen and Samuel Gompers, Industrial Workers of the World, Kansas Court of Industrial Relations, the Ku Klux Klan, National Nonpartisan League, Republican Party politics, and the Republican National Convention in 1920. Correspondents include Will H. Hays, Harold L. Ickes, Alfred M. Landon, Arthur H. Vandenberg, William Allen White, and Leonard Wood.
Publisher and governor of and U.S. senator from Kansas.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Gompers, Samuel, -- 1850-1924.; Hays, Will H. -- 1879-1954 -- Correspondence; Ickes, Harold L. -- 1874-1952 -- Correspondence; Landon, Alfred M. -- 1887-1987 -- Correspondence; Vandenberg, Arthur H. -- 1884-1951 -- Correspondence; White, William Allen, -- 1868-1944 -- Correspondence; Wood, Leonard, -- 1860-1927 -- Correspondence; Allen family; Kansas. -- Court of Industrial Relations; Great Lakes-St. Lawrence Tidewater Association; Industrial Workers of the World; Ku Klux Klan (1915- ); National Nonpartisan League; Near East Relief (Organization); Republican Party (U.S. : 1854- ); Save the Children (U.S.); Child welfare -- Societies, etc; Labor unions; Kansas -- Politics and government -- 1865-1950.; United States -- Politics and government -- 1901-1953.; Governors -- Kansas; Publishers; Senators, U.S. Congress -- Kansas